Influence Of Glucose And Yeast Extract Toward Production Of Pseudomonas Aeruginosa-Protease Inhibitor From Chromohalobacter Sp. 6a3 (Bacteria Associated With Sponge Xetospongia Testudinaria) - Tati Nurhayati; Maggy Thenawidjaja; Lilis Nuraida; Sri Budiarti Poerwanto (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
One way to inhibit protease activity is search is compound which can inhibit the enzyme known as protease inhibitor. The bacteria associated with sponge Xetospongia testudinaria, Chromohalobacter sp. 6A3, as producer Pseudomonas aeruginosa-protease inhibitor. Because the compound is important, determination medium composition for producing is very important to be conducted. The purpose of this research was to determinate the glucose and yeast extract consentration accurately so protease inhibitor would be produced in a short time. The accurate medium composition for producing the protease inhibitor were 0.1%(w/v) yeast extract; 0.05% (w/v) glucose; 0.5%(w/v) special peptone; 0.2%(v/v) trace element; and 2%(w/v) NaCl at pH 7.Keywords: Chromohalobacter sp., protease inhibitor, sponges.